México, el voto por la democracia - Aguilar, Luis F.; Argüelles, Antonio; Villa Aguilera, Manuel (México, D.F. : M.A. Porrúa, 1994)
"Collection of essays, some written by Mexico's leading analysts, explores Mexican electoral politics during the 1990s. Topics include the impact of violence, NGOs, public opinion polls, reforms within the PRI, and the electoral process itself. Very useful election data from 1988-94"--Handbook of Latin American Studies, v. 57.
Incluye referencias bibliográficas.
Descripción basada en recurso en línea; Título de la página del título en PDF (e-libro, visto June 08, 2015).
Recurso electrónico. Santa Fe, Arg.: e-libro, 2015. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a e-libro.
Keywords: Participación política -- México.; Elecciones -- México.; Partidos políticos -- México.; Democracia -- México.; Political participation -- Mexico; Elections -- Mexico; Political parties -- Mexico; Democracy -- Mexico; Libros electrónicos.